2015
DOI: 10.1186/s13071-015-0853-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeat human blood feeding on Wolbachia density and dengue virus infection in Aedes aegypti

Abstract: BackgroundThe introduction of the endosymbiotic bacterium, Wolbachia into Aedes aegypti populations is a novel approach to reduce disease transmission. The presence of Wolbachia limits the ability of the mosquito to transmit dengue virus (DENV) and the strength of this effect appears to correlate with Wolbachia densities in the mosquito. There is also some evidence that Wolbachia densities may increase following the consumption of a bloodmeal. Here we have examined whether multiple blood feeds lead to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…aegypti populations. This sharply contrasts previous studies where Wolbachia infection significantly reduced the proportion of individuals infected with other flaviviruses such as DENV (Amuzu & McGraw, 2016; Amuzu, Simmons, & McGraw, 2015; Bian et al., 2013; Frentiu et al., 2014; Moreira et al., 2009; Walker et al., 2011), Zika (Aliota et al., 2016; Dutra et al., 2016), and YFV (van den Hurk et al., 2012). Our findings are, however, supported by studies performed in Cx.…”
Section: Discussioncontrasting
confidence: 94%
“…aegypti populations. This sharply contrasts previous studies where Wolbachia infection significantly reduced the proportion of individuals infected with other flaviviruses such as DENV (Amuzu & McGraw, 2016; Amuzu, Simmons, & McGraw, 2015; Bian et al., 2013; Frentiu et al., 2014; Moreira et al., 2009; Walker et al., 2011), Zika (Aliota et al., 2016; Dutra et al., 2016), and YFV (van den Hurk et al., 2012). Our findings are, however, supported by studies performed in Cx.…”
Section: Discussioncontrasting
confidence: 94%
“…Recent work suggests that repeated blood feeding does not affect interference against DENV in Ae . aegypti [114]. While a sucrose-based diet is unlikely to be perfectly reflective of mosquito carbohydrate intake in the field, our diets did induce varying levels of nutritional stress, which could be similar to what mosquitoes in a heterogeneous environment might experience.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti mosquitoes designated w Mel.F and Wildtype [31,42], respectively. The w Mel.F mosquito line was collected in 2012 from field release sites in Cairns, Australia [18] while the Wildtype line was collected in 2014 from Babinda, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that Wolbachia is found at different densities in various tissues of the mosquito body, with the ovaries and Malpighian tubules tending to have high densities [14,21,28,30,31]. Osborne et al ., [32] have suggested that Wolbachia density within the head, gut and Malpighian tubules correlated with the ability to mediate protection against DCV in D .…”
Section: Introductionmentioning
confidence: 99%